2015
DOI: 10.1017/s0956792515000546
|View full text |Cite
|
Sign up to set email alerts
|

A line sink in a flowing stream with surface tension effects

Abstract: We examine a problem in which a line sink causes a disturbance to an otherwise uniform flowing stream of infinite depth. We consider the fully non-linear problem with the inclusion of surface tension and find the maximum sink strength at which steady solutions exist for a given stream flow, before examining non-unique solutions. The addition of surface tension allows for a more thorough investigation into the characteristics of the solutions. The breakdown of steady solutions with surface tension appears to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…where This behaviour was described in more detail in the unbounded case by Hocking et al (2015). Larger values of truncation resulted in increasing wave activity on the surface and a decrease in the maximum Froude number.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
See 2 more Smart Citations
“…where This behaviour was described in more detail in the unbounded case by Hocking et al (2015). Larger values of truncation resulted in increasing wave activity on the surface and a decrease in the maximum Froude number.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…tension was considered in Forbes & Hocking (1993), and withdrawal in the presence of a background flow by Holmes & Hocking (2015). In both cases non-uniqueness was found in the solution space.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the number of mesh points typically used is roughly 500 < N < 2000. [30][31][32][33][34][35][36][37] The increased number of points can allow for a solution with much higher resolution or over a much larger domain. In an attempt to quantify the benefits of using a large number of grid points, we perform a brief convergence study.…”
Section: Flow Past a Pressure Distributionmentioning
confidence: 99%
“…In the two-dimensional case (line sink [4,9]), this was found to provide considerable information about the flows including nonuniqueness in the solution space. Holmes and Hocking [14] recently showed that this nonuniqueness also occurs when the submerged sink is situated in a flowing stream.…”
Section: Introductionmentioning
confidence: 95%